Pharmacy Students’ Perceptions of Generic Medicines in Southern Vietnam - Quang Vo, Dr. Trung (Asian Journal of Pharmaceutics (AJP), 2018)
Context: Various studies concerning the knowledge of pharmacy students regarding generic medicines have been conducted worldwide although this issue has not previously been investigated in Vietnam. Aims: The present study therefore aims to assess the knowledge of pharmacy students regarding generic medicines in Southern Vietnam. Materials and Methods: A cross-sectional survey study was conducted between January and April 2017. A total of 608 undergraduate pharmacy students from various universities in Southern Vietnam were questioned using a 22-item questionnaire. Statistical Analysis used: The Chi-square, t-test, and analysis of variance were manipulated to calculate the association between the study variables. Results: Some 800 forms were initially distributed, which led to an effective response rate of 76.0% when 608 forms were returned by 306 students from private universities and 302 students from public universities. The numbers of participants who had previously heard of the brand name and generic medicines were 93.3% and 90.6%, respectively. The major sources of students’ knowledge included textbooks (72.7%) and lectures (82.6%). Almost 90% of students exhibited the ability to distinguish generic and brand name medicines. Of the ten questions investigating participants’ knowledge of generic medicines, the average score of the 608 students was 5.19 ± 2.43. In this regard, the public university students scored higher with 5.65 ± 2.61 than the private students with 4.73 ± 2.15 (t = −4.770, P < 0.001). Conclusions: In general, the lack of awareness among pharmacy students varied between universities so that both the education system and the government should pay a greater attention to the education of future pharmacists.